Efficacy of a combination of praziquantel and artesunate in the treatment of urinary schistosomiasis in Nigeria - Inyang-Etoh, P.C.; Ejezie, G.C.; Useh, M.F.; Inyang-Etoh, E.C. (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2009)
The combined effects of praziquantel and artesunate in the treatment of urinary schistosomiasis were assessed among 312 randomly selected schoolchildren aged 4–20 years in Adim community, Nigeria. In the preliminary screening, infection was confirmed in 327 (38.5%) of the 850 subjects screened. Infected subjects who reported for treatment were then divided into six treatment groups of 52 subjects each; 44 subjects in each group completed their treatment regimens and submitted their urine for post-treatment assessment. Praziquantel and artesunate were administered orally at 40 mg/kg and 4 mg/kg body weight, respectively. Adverse effects due to drug reactions were assessed 72 h after medication and all perceived episodes of illness were treated. Morbidity indicators were assessed 56 days after the final dose of the drug regimens. All treatment regimens were well tolerated. The cure rates were 72.7% in the praziquantel plus placebo-treated group and 70.5% in the artesunate plus placebo group, while the artesunate plus praziquantel group had the highest cure rate (88.6%). Haematuria and proteinuria were extensively reduced after treatment with the three drug regimens. This study confirmed that the treatment of urinary schistosomiasis with the combination of praziquantel and artesunate is safe and more effective than treatment with either drug alone.